Ways of decision of problem of forming for the cadets of the special qualities, need the militiaman to successful counteract against the armed attack - Bondarenko V.V (Kharkov National Pedagogical University, 2010)
Directions of forming of the special qualities of workers of militia are certain. Information is systematized about the real collisions of workers of militia with criminals. Conformities to law are rotined in the conduct of a be out for scalps criminal. The necessity of development and perfection of the special qualities of workers of militia is exposed. The terms of the hidden attack of criminal are considered. The necessity of mastering of knowledge is rotined about preparatory motions of the armed criminal. Directions of perfection of the special physical and psychical qualities, forming of abilities and skills of implementation of receptions of disarmament, are resulted.